140k views
1 vote
HELP PLEASE!!! ♡

Solve by using system of equations and substatuion

-3x - y = -13
x + 2y = 6

*Show work! ​

User Nitha Paul
by
5.4k points

1 Answer

1 vote

Answer:

x=4, y=1. (4, 1).

Explanation:

-3x-y=-13

x+2y=6

x=6-2y

-3(6-2y)-y=-13

-18+6y-y=-13

-18+5y=-13

5y=-13-(-18)

5y=-13+18

5y=5

y=5/5

y=1

x+2(1)=6

x+2=6

x=6-2

x=4

User Andrewz
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.